Aktivitas residu protein Cry1Ac Pada lahan yang ditanami kapas transgenik-Bt di Bajeng dan Soppeng, Sulawesi Selatan - Purnama Hidayat; Djoko Prijono (Jurnal Entomologi Indonesia, 2006)
Soil samples were collected from each plot at the two field sites at 0, 1, 3, and 5 months after planting, and at one-month intervals after harvest for three months. Soil suspension from each sample was mixed with agar based diet (1 g soil/20 ml soil-diet mixture) then was presented to neonate larvae of H. armigera. Two reference standards were used, i.e. pure Cry1Ac protein (0.165 x 104 to 1.436 x 105 ng per ml of the proteindiet mixture) and non-Bt-soil spiked with Cry1Ac protein (0.11 x 104 to 9.573 x 104 ng per ml of the soil-diet-mixture). Larval mortality was recorded at 7 days of treatment. In both reference standards, mortality of H. armigera larvae occurred in a concentrationdependent fashion, i.e. larval mortality increased with the increase in Cry1Ac protein concentration, with LC50 of 0.95 x 104 and 1.65 x 104 ng/ml, respectively, for the pure protein and spiked non-Bt-soil standards. Result of the bioassay of soil samples from the field sites showed the residues from both transgenic cotton soils did not cause any mortality (0%) in the test insects. This indicates that the concentrations of Cry1Ac residue in soil at the study sites were very low (in the second standard, Cry1Ac at a concentration of 0.33 x 104 ng/ml caused about 10% larval mortality).